Table of Integrals - Forms Involving `cosh ax`

The integrals below involve `cosh ax`.

1) `int  cosh ax  dx = (sinh ax)/a`

2) `int  x*cosh ax  dx = (x*sinh ax)/a-(cosh ax)/a^2`

3) `int  x^2 cosh ax  dx = -(2x cosh ax)/a^2+(x^2/a+2/a^3)sinh ax`

4) `int  (cosh ax)/x  dx = ln x+(ax)^2/(2*2!)+(ax)^4/(4*4!)+(ax)^6/(6*6!)+...`

5) `int  (cosh ax)/x^2  dx = -(cosh ax)/x+a int  (sinh ax)/x  dx`

                    **[See integral #4 int the table involving `sinh ax`]

6) `int  1/(cosh ax)  dx = 2/a tan^-1 e^(ax)`

7) `int  x/(cosh ax)  dx = 1/a^2{(ax)^2/2-(ax)^4/8+(5(ax)^6)/144+...+((-1)^nE_n(ax)^(2n+2))/((2n+2)(2n)!)+...}`

8) `int  cosh^2 ax  dx = x/2+(sinh ax*cosh ax)/(2a)`

9) `int  x*cosh^2 ax  dx = x^2/4+(x sinh 2ax)/(4a)-(cosh 2ax)/(8a^2)`

10) `int  1/(cosh^2 ax)  dx = (tanh ax)/a`

11) `int  cosh ax*cosh px  dx = (sinh(a-p)x)/(2(a-p))+(sinh(a+p)x)/(2(a+p))`

12) `int  cosh ax*sin px  dx = (a sinh ax*sin px-p cosh ax*cos px)/(a^2+p^2)`

13) `int  cosh ax*cos px  dx = (a sinh ax*cos px+p cosh ax*sin px)/(a^2+p^2)`

14) `int  1/(cosh ax+1)  dx = 1/a tanh((ax)/2)`

15) `int  1/(cosh ax-1)  dx = -1/a coth((ax)/2)`

16) `int  x/(cosh ax+1)  dx = x/a tanh ((ax)/2)-2/a^2 ln cosh ((ax)/2)`

17) `int  x/(cosh ax-1)  dx = -x/a coth ((ax)/2)+2/a^2 ln sinh ((ax)/2)`

18) `int  1/(cosh ax+1)^2  dx = 1/(2a)tanh((ax)/2)-1/(6a)tanh^3((ax)/2)`

19) `int  1/(cosh ax-1)^2  dx = 1/(2a) coth((ax)/2)-1/(6a) coth^3((ax)/2)`

20) `int  1/(p+q cosh ax)  dx = 2/(asqrt(q^2-p^2))tan^-1((qe^(ax)+p)/sqrt(q^2-p^2))`

                              OR `=1/(asqrt(p^2-q^2))ln((qe^(ax)+p-sqrt(p^2-q^2))/(qe^(ax)+p+sqrt(p^2-q^2)))`

21) `int  1/(p+q cosh ax)^2  dx = (q sinh ax)/(a(q^2-p^2)(p+q cosh ax))-p/(q^2-p^2) int  1/(p+q cosh ax)  dx`

22) `int  1/(p^2-q^2 cosh^2 ax)  dx = 1/(2apsqrt(p^2-q^2)) ln ((ptanh ax+sqrt(p^2-q^2))/(p tanh ax-sqrt(p^2-q^2)))`

                                  OR `=(-1)/(apsqrt(q^2-p^2))tan^-1((p tanh ax)/sqrt(q^2-p^2))`

23) `int1/(p^2+q^2 cosh^2 ax)  dx = 1/(2apsqrt(p^2+q^2)) ln((p tanh ax+sqrt(p^2+q^2))/(p tanh ax-sqrt(p^2+q^2)))`

                                 OR `=1/(apsqrt(p^2+q^2)) tan^-1((p tanh ax)/sqrt(p^2+q^2))`

24) `int  x^m cosh ax  dx = (x^m sinh ax)/a-m/a int  x^(m-1) sinh ax  dx`

                    **[See integral #18 in the table involving `sinh ax`]

25) `int  cosh^n ax  dx = (cosh^(n-1) ax*sinh ax)/(an)+(n-1)/n int  cosh^(n-2) ax  dx`

26) `int  (cosh ax)/x^n  dx = (-cosh ax)/((n-1)x^(n-1))+a/(n-1) int  (sinh ax)/x^(n-1)  dx`

                    **[See integral #20 in the table involving `sinh ax`]

27) `int  1/(cosh^n ax)  dx = (sinh ax)/(a(n-1)cosh^(n-1) ax)+(n-2)/(n-1) int  1/(cosh^(n-2) ax)  dx`

28) `int  x/(cosh^n ax)  dx = (x sinh ax)/(a(n-1)cosh^(n-1) ax)+1/((n-1)(n-2)a^2 cosh^(n-2) ax)+(n-2)/(n-1) int  x/(cosh^(n-2) ax)  dx`